The Constitutional Hurdles to Exercise Secession Right and Arguments on Its Inclusion in the Ethiopian Constitution - Shambel, Teshale (Journal of Legal Studies, 2020)
The right to self-determination is one of the human rights enshrined under the Ethiopian constitution. It is also one of the rights mentioned under ICCPR and ICESCR as well as the constitutions of different countries.  Being unique to many other human rights instruments and constitutions in the world, the Ethiopian constitution includes the unconditional right to secession as a part of self-determination for every one of the ethnic groups (nations, nationalities, and people) in the country. As argued among many scholars, the inclusion of unconditional secession as a part of self-determination right in the Ethiopian constitution was based on the wrong narrative that nations, nationalities and people in the country were oppressed. Thus, it is a point of political debate between elites and became the major cause of widening the divergence among views of different political parties in the country.  Of course, within the constitution, there are hurdles that can potentially deny exercising of this right. Therefore, this study qualitatively analyses the impracticability of secession and unacceptability of narratives to its inclusion in the constitution of the federal democratic republic of Ethiopia.